Stop talking, start communicating : counterintuitive secrets to success in business and in life - Tumlin, Geoffrey (McGraw Hill-Ascent Audio, 2013)
PLAY DUMB. BE BORING. DON'T SOLVE PROBLEMS. AND ABOVE ALL, DON'T BE YOURSELF. Not exactly what you'd expect to hear from a communication expert, but these counterintuitive strategies are precisely what we need to interact productively and meaningfully in today's digital world. Our overreliance on quick, cheap, and easy means of "staying connected" is eroding our communication skills. Speed steamrolls thoughtfulness; self-expression trumps restraint. Errors and misunderstandings increase. And our relationships suffer. With startling insights and a dash of humor, Stop Talking, Start Communicating combines scientific research with real-world strategies to deliver a proven approach to more effective communication. "Only Geoffrey Tumlin could write a book about a serious problem--our mounting communication deficiencies--and make me laugh and learn all the way through it. Witty, smart, and 100 percent accurate, Stop Talking, Start Communicating points the way to a better conversational future."--Tina Morris, managing director at Standard & amp; Poor's "An elegantly analytical, accessible, and enjoyable guide to improving interpersonal communication, Stop Talking, Start Communicating is a key resource for anyone who wants to be a difference-making leader, manager, or team member." -- Eduardo Sanchez, deputy chief medical officer of the American Heart Association